Association of Body-Weight Fluctuation With Outcomes in Heart Failure With Preserved Ejection Fraction - Li, Yi; Yu, Yuan; Wu, Yuzhong; Liang, Weihao; Dong, Bin; Xue, Ruicong; Dong, Yugang; Zhu, Wengen; Huang, Peisen (Frontiers in Cardiovascular Medicine, 2021)
Aims: To investigate the relationship between body-weight fluctuation and risks of clinical outcomes in patients with heart failure with preserved ejection fraction (HFpEF). Methods and Results:We measured intra-individual variations in body weight from baseline and follow-up visits in 1,691 participants with HFpEF from the Americas from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial. The primary endpoint was any cardiovascular events (a composite of death from cardiovascular disease, non-fatal myocardial infarction, aborted cardiac arrest, or hospitalization for HF). The body-weight fluctuation was measured according to average successive variability and high variability was defined as greater than or equal to the median. After adjustment for risk factors, mean body weight and weight change, each increase of 1 standard deviation in body-weight variability was significantly associated with increased risks of any cardiovascular events (hazard ratio [HR] 1.23, 95% confidence interval [CI] 1.15–1.33, P < 0.001). Patients with high variability had a 47% increased risk of any cardiovascular events and 27% increased risk of all-cause death compared with those with low variability. Such association was similar among patients with New York Heart Association functional class I/II vs. III/IV, obesity vs. non-obesity, and weight loss, gain vs. stability (the P-values for interaction were all insignificant). Conclusion: Among patients with HFpEF, body-weight fluctuation was associated with increased risks of cardiovascular events independent of traditional cardiovascular risk factors, and regardless of HF severity, baseline weight or weight change direction. Clinical Trial Registration: Aldosterone antagonist therapy for adults with heart failure and preserved systolic function (TOPCAT), https://clinicaltrials.gov, identifier [NCT00094302].